Presacral myelolipoma, case report and literature review. (September 2020) - Andriandi; Cleven, A.H.G.; Hanff, D.F.; Hartgrink, H.; Dijkstra, P.D.S.
Abstract: Introduction: Myelolipomas are very rare benign tumours consisting of hematopoietic cells and mature adipose tissues. They are most commonly found in the adrenal glands. However, there have been several reported cases of extra-adrenal myelolipomas, most commonly in the presacral region. Nearly all presacral lesions are small and asymptomatic; thus, most are discovered incidentally on imaging studies. Presentation of case: We report two cases of presacral myelolipomas. The first is a 48-year-old female presenting with atypical back pain, found to have a mass in her presacral region with a size of 3, 3 cm. The second case is a 59-year-old female, who presented for evaluation of a hip fracture, found to have a 4, 7 cm presacral lesion. Both presacral myelolipomas were discovered incidentally and were confirmed by percutaneous guided fine-needle aspiration biopsy. Both were treated conservatively. Discussion: Accepted indications for the surgical excision of myelolipomas are symptomatic tumour, size >4 cm, metabolically active tumour, and a suspicion of malignancy on an imaging study. However, previous reports have documented that nearly half of the conservatively managed myelolipomas with a mean initial size of 5, 1 cm, has increased in size or became symptomatic over a 3-years period. Conclusion: We conclude that symptomatic presacral myelolipomas or lesions larger than 4 cm should be en-bloc resected, and we present an intuitive decision-making algorithm. Highlight: Presacral myelolipoma is an orphan disease. We emphasize the role of imaging in the differential diagnosis of presacral tumours. Percutaneous biopsy is rarely indicated to distinguish the diagnosis. We recommend enbloc resection for lesion larger than 4 cm. We present an intuitive decision-making algorithm.